Early leaf removal as a strategy to control botrytis cinerea rot in cabernet sauvignon grapevine at high altitude regions Desfolha precoce como estratégia de controle da podridão de botrytis cinerea na videira cabernet sauvignon em regiões de altitude - Wurz D.A.* (2017)
© 2017, Universidade Estadual Paulista (UNESP). All rights reserved.Botrytis cinerea is one of the most important pathogens in the highlands of Santa Catarina State. This study aimed to evaluate the influence of different times of leaf removal on the progress of B. cinerea rot in Cabernet Sauvignon grapevine. Assays were conducted in the 2014/2015 and 2015/2016 growing seasons in a commercial vineyard located at 1230m (a.s.l.) in São Joaquim Municipality, Santa Catarina State (28º 17’ 39” S and 49º 55’ 56” W). The variety Cabernet Sauvignon was grafted on Paulsen 1103 rootstock, conducted in vertical shooting positioning, 3.0m x 1.5m spacing, and covered with hail protection net. Treatments consisted in leaf removal at the phenological stages: full bloom, buckshot berries, pea-sized berries, veraison, 15 days after veraison and plants not subjected to leaf removal. The disease was biweekly measured in bunches from the first symptoms to harvest. Disease progress curves were elaborated and compared according to: beginning of symptoms, time to maximum disease incidence and severity, maximum disease incidence and severity, and area under the disease incidence and severity progress curve. Results evidenced that early leaf removal should be recommended as management strategy to control B. cinerea in Cabernet Sauvignon grapevine grown in the highlands of Santa Catarina.